(untitled) (Research, Society and Development, 2020)
Conduct an epidemiological analysis of suicide in the northeastern region from Brazil between 2014 and 2018. This is an epidemiological, documentary, retrospective, descriptive study, with a quantitative approach on suicide rates found in the northeast region from Brazil in the period between 2014 and 2018. The data were obtained from the Information System in the official database of SINAN, from the Department of Informatics of Unified Health System (DATASUS). It was observed that the prevalence of deaths registered by suicide according to the age group occurs in individuals from 30 to 39 years old, with a significant increase in the ages of 15 to 19 years old. It was evidenced that males commit more self-injurious acts than females and regarding marital status, the single and low-educated individual stands out as the highest number of deaths due to this cause. There was an urgent need for suicide prevention measures, as there is a tendency to increase each year, early intervention appears in order to protect life and the damage caused by it.